Pengaruh Pemberian Tunjangan Kinerja Terhadap Pelayanan Publik pada Dinas Pertanian Kabupaten Sidenreng Rappang - ST Maryam (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
Abstract This research is done to determine the effect of incentive to increase performance on public services at The Department of Agriculture and Plantation, along with all influencing factors. Performance incentive is an incentive given to Country Civic-duty (pre) Employee (what we call Pegawai Negeri Sipil and Calon Pegawai Negeri Sipil) based on attendance and performance to serve people. The employee’s capability to serve people is indeed the key factor to determine whether the performance incentive has reached its goal. Therefore this research is needed to analyze the quality of given services along with all the factors influencing the quality of public services. This research is using descriptive method, the samples takes all members of population and uses questionnaires to interview all forty (40) respondents serving public services. The result shows that organization’s performance in public service given the performance incentive has increased according to almost all respondents. The key factor is education and training, the higher education level and more frequent training would make a better service quality.